Final overall survival analysis of a phase II trial evaluating vinorelbine and lapatinib in women with ErbB2 overexpressing metastatic breast cancer. Issue 6 (December 2015) - Janni, Wolfgang; Sarosiek, Tomasz; Karaszewska, Boguslawa; Pikiel, Joanna; Staroslawska, Elzbieta; Potemski, Piotr; Salat, Christoph; Brain, Etienne; Caglevic, Christian; Briggs, Kathryn; Mahood, Kim; DeSilvio, Michelle; et al.
Abstract: Lapatinib plus capecitabine (lap+cap) is approved as treatment for patients with human epidermal growth factor receptor 2 (HER2)-positive metastatic breast cancer (MBC), who have progressed on prior trastuzumab in the metastatic setting. We previously reported progression-free survival (PFS), overall survival (OS) and safety results from this open-label, multicentre, phase II study (VITAL; NCT01013740) conducted in women with HER2 positive MBC, to evaluate the efficacy and safety of lap plus vinorelbine (lap+vin), an important chemotherapy option for MBC, compared with lap+cap. In total, 112 patients were randomised 2:1 to treatment with lap+vin (N = 75) or lap+cap (N = 37). Results showed that the median PFS (primary endpoint) and OS (secondary endpoint) post-randomisation were comparable between treatment arms, with no new safety signals detected. Here, we assessed the final OS in this study at 40 months post-randomisation. At the time of final analyses, 24 (32%) patients were ongoing in the lap+vin arm, compared with 14 (38%) patients in the lap+cap arm (92% in both arms had discontinued treatment). Median OS in the lap+vin arm was 23.3 months (95% confidence intervals [CI]: 18.5, 31.1), compared with 20.3 months (95% CI: 16.4, 31.8) in the lap+cap arm. The median follow-up in the lap+vin arm was 18.86 months (95% CI: 10.68, 26.02), compared with 19.38 (95% CI: 25.56) months in the lap+cap arm. Similar rates of death (56–57%) were observed in both arms. The final OS was consistent with the previously reported data and suggest that lap+vin offers an effective treatment option for women with HER2-positive MBC. Highlights: Previous findings from VITAL showed comparable OS between lap+vin and lap+cap. Here we report final OS in this study at 40 months post-randomisation 32% patients were ongoing in the lap+vin arm; 38% patients in the lap+cap arm. Median OS was 23.3 months in the lap+vin arm and 20.3 months in the lap+cap arm. Lap+vin may offer an effective treatment option for women with HER2-positive MBC.